Care pathway and organisational features driving patient experience: Statistical analysis of large NHS datasets - Flott,K; Darzi,A; Mayer,E (BMJ Open, 2018)
Objective: The aim of this study was to identify the care pathway and organisational factors that predict patient experience Design: Statistical analysis of large NHS datasets Setting & participants: England; Acute NHS organisational-level dataPrimary and secondary outcome measures: The relationship of care pathway and organisational variables to organisation-level patient experience Results: A framework of 18 care pathway and organisational variables were created based on the existing literature. Eleven of these correlated to patient experience in univariate analyses. Multi-collinearity tests resulted in one of the 11 variables holding a correlation to another variable larger than r=0.70. A significant multi-linear regression equation including the final ten variables was found (F(10,108) = 6.214, p < 0.00), with an R^2 of 0.365. Two variables were significant in predicting better in patient experience: Amount of support to clinical staff (Beta = 0.2, p = 0.02) and the proportion of staff who would recommend the trust as a place to work or receive treatment (Beta = 0.26, p = 0.01). Two variables were significant in predicting a negative impact on the patient’s rating of their experience: Number of patients spending over 4 hours from decision to admit to admission (Beta =-1.99 p = 0.03) and the percentage of estates and hotel services contracted out (Beta = -0.23, p = 0.01). Conclusions: These results indicate that augmenting clinical support and investing in the mechanisms that facilitate positive staff experience is essential to delivering appropriate, informative and patient-centric care. Reducing wait times and the extent of external contracting within hospitals is also likely to improve patient ratings of experience. Understanding the relationship between patient experience and objective, measurable organisational features promotes a more patient-centric interpretation of quality and compels a better use of patient experience feedback to drive im